ANALYSIS OF PSYCHOSOCIAL THROUGH THE SOCIAL INJUSTICE IN UNFORTUNATE EVENTS FILM (2004) - Natasya, Ajeng Tialin (Universitas Negeri Surabaya, 2022)
Psychosocial is an important study to be understood and studied by everyone to know oneself as the basis for socializing. This study is also very important for people who have experienced social injustice, like the Baudelaire children, Violet, Klaus, and Sunny. Because the study can help the characters to know themselves to live their new life, their personality development is described through several phases called